2022
DOI: 10.3390/ijms23147740
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances Regarding the Molecular Mechanisms of Triterpenic Acids: A Review (Part I)

Abstract: Triterpenic acids are phytocompounds with a widespread range of biological activities that have been the subject of numerous in vitro and in vivo studies. However, their underlying mechanisms of action in various pathologies are not completely elucidated. The current review aims to summarize the most recent literature, published in the last five years, regarding the mechanism of action of three triterpenic acids (asiatic acid, oleanolic acid, and ursolic acid), corelated with different biological activities su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 263 publications
0
25
0
3
Order By: Relevance
“…The investigation of the apoptotic mechanism induced by pentacyclic triterpenic acids revealed that they can act as mitocans (mitochondria targeting anticancer agents), which trigger apoptosis through the intrinsic pathway [ 42 ]. To investigate the finer mechanisms of action of the three newly synthesized esters, we performed high-resolution respirometry studies in A375 human melanoma cells as well as in HaCaT normal cells; previous studies using the same protocol revealed that BA stimulation triggered an overall inhibition of cellular respiration in A375 melanoma cells as indicated by the inhibition of basal and active respiration, as well as of maximal uncoupled respiration [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The investigation of the apoptotic mechanism induced by pentacyclic triterpenic acids revealed that they can act as mitocans (mitochondria targeting anticancer agents), which trigger apoptosis through the intrinsic pathway [ 42 ]. To investigate the finer mechanisms of action of the three newly synthesized esters, we performed high-resolution respirometry studies in A375 human melanoma cells as well as in HaCaT normal cells; previous studies using the same protocol revealed that BA stimulation triggered an overall inhibition of cellular respiration in A375 melanoma cells as indicated by the inhibition of basal and active respiration, as well as of maximal uncoupled respiration [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Эта группа соединений содержит широкий спектр молекул, которые участвуют во многих биологических реакциях. Так, тритерпены могут вызывать миграцию клеток, пролиферацию и отложение коллагена, участвуя в восстановлении тканей [22,23]. Следует отметить, что одним из лидеров по содержанию последних является масло ши (масло карите), используемое в продуктах по уходу за кожей.…”
Section: возможные методики профилактики и лечения радиодерматитаunclassified
“…104 МЕДИЦИНСКИЙ СОВЕТ 2022;16 (22): [103][104][105][106][107][108][109][110] Поддерживающая терапия ВВЕДЕНИЕ Радиодерматит (лучевой дерматит, радиационноинду цированные кожные реакции или радиационное поражение) является значимым побочным эффектом воздействия ионизирующего излучения на кожу в ходе лечения онкологических заболеваний. В частности, у 85-95% больных раком, получаю щих лучевую терапию, развивается какая-либо форма лучевого поражения кожных покровов, включая эритему, сухую или влажную десквамацию [1,2].…”
unclassified
“…This review represents the continuation of our recently published paper regarding the mechanisms of action of several triterpenic acids of therapeutic value including asiatic, oleanolic, and ursolic acid [ 19 ]. The current paper depicted the most recent (last 5 years) studies on the MOA of betulinic acid, boswellic acid, glycyrrhetinic acid, madecassic acid, moronic acid, and pomolic acid in order to provide scientists with updated and accessible material on the topic that could set in motion future original studies.…”
Section: Introductionmentioning
confidence: 99%